2016
DOI: 10.5194/angeo-34-581-2016
|View full text |Cite
|
Sign up to set email alerts
|

Daytime twin-peak structures observed at southern African and European middle latitudes on 8–13 April 2012

Abstract: Abstract. Daytime twin-peak structures, also known as biteout or diurnal double-maxima structures, are ionospheric phenomena in which the diurnal ionospheric trend shows two peaks (instead of the normal one) during the daytime. This study reports on first simultaneous observations of these structures in the Global Positioning System and ionosonde measurements from the southern African and European middle-latitude stations during a mostly quiet geomagnetic condition period of 8-13 April 2012, which indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Additionally, the ionospheric DDM with different occurrence times at middle latitudes could be attributed to different generation mechanisms. Previous studies suggested that the poleward neutral winds play a dominant role in the generation of ionospheric DDM at middle latitudes (Katamzi et al, 2016;Zhang et al, 2000). Abur-Robb (1969) suggested that the poleward neutral winds during 4:30-16:30 LT could cause the ionospheric depletion around noontime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the ionospheric DDM with different occurrence times at middle latitudes could be attributed to different generation mechanisms. Previous studies suggested that the poleward neutral winds play a dominant role in the generation of ionospheric DDM at middle latitudes (Katamzi et al, 2016;Zhang et al, 2000). Abur-Robb (1969) suggested that the poleward neutral winds during 4:30-16:30 LT could cause the ionospheric depletion around noontime.…”
Section: Discussionmentioning
confidence: 99%
“…The ionospheric DDM occurs generally at low latitudes and in the equatorial region, which is suggested to be associated with the effect of upward E×B drift that produces the equatorial ionization anomaly (EIA; Abur-Robb, 1969;Adebesin et al, 2018;Baxter & Kendall, 1968;Rajaram, 1977;Rastogi, 1966). It can also be observed at middle latitudes, as a result of dynamic processes in terms of poleward neutral winds and thermal expansion (Abur-Robb, 1969;Katamzi et al, 2016;Khan et al, 1985;Kohl & King, 1967;Saryo et al, 1989;Zhang et al, 2000). In addition, the ionospheric DDM can be connected with substorms and storms (Pi et al, 1993;Sojka et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible candidate responsible for the decrease of plasma density associated with a downward plasma transport is the poleward meridional neutral wind. Based on the ionosonde measurements at specific locations, plasma density depletions were observed and suggested to be associated with downward ion drift driven by poleward neutral winds (e.g., Katamzi et al, 2016;Saryo et al, 1989). Mikhailov et al (2007) demonstrated that the quiet time negative ionospheric disturbances always corresponded to strong poleward neutral winds according to the Millstone Hill ISR observations.…”
Section: Discussionmentioning
confidence: 99%
“…The daytime noon bite-out is caused by the motion of plasma blown away from the dip equator into the hemispheres. The vertical plasma drift is the combined result of the zonal electric field and the thermospheric winds owing to the geomagnetic field-aligned motion of ions (Katamzi et al, 2016). Subsequently, the buildup in the electron density continues and the second peak in NmF2 forms at about 1500-1700 hr (postnoon peak) with values of 8.8 × 10 11 m −3 during equinoxes, 9.5 × 10 11 m −3 in summer, and 5.7 × 10 11 m −3 in winter.…”
Section: Eej Current and Nmf2mentioning
confidence: 99%